V. S. Merlin About the Problem of Psychological Training in the Pedagogical Higher School (Celebrating the 115th Anniversary of the Scientist) - B. A. Vyatkin; M. P. Shchukin (Obrazovanie i Nauka)
The paper is devoted to the scientific contribution of V. S. Merlin – one of the prominent psychologists of the former Soviet Union, the chairman of the Ural Branch of the Psychologists Society for over 30 years. The authors make the retrospective analysis of his views and experience, and give some facts of his biography. His idea of holistic integral approach to the man solving practical tasks involving the diversity of somatic, neuro-physiological, psychological and social aspects in their close interrelation, still remains relevant.The paper summarizes the experience of the Psychology Department at Perm State Pedagogical University, headed by the scientist for a long time. The considerable contribution of V. S. Merlin and his followers into the theoretical foundation of pedagogical education gets the greater importance now - in the context of democratization and humanization of society, and transition from the subject-oriented to human-oriented education.